Measurement of the Femoral Anteversion Angle in Medium and Large Dog Breeds Using Computed Tomography - Al Aiyan, Ahmad; Richardson, Ken; Manchi, George; Ginja, Mário; Brunnberg, Leo (Frontiers in Veterinary Science, 2021)
To promote the development of an optimally functional total hip prosthesis for medium and large dog breeds, accurate measurements of the normal anatomy of the proximal femur and acetabular retroversion are essential. The aim of the current study was to obtain precise normal values of the femoral anteversion angle using computed tomography on cadavers of mature dogs with normal hip joints of both medium and large breeds. Based on the length of their femora 58 dogs were allocated either to group I: ≤ 195 mm or group II: >195 mm. In the study the femoral anteversion angle (FAA) was measured on each femur using multi-slice spiral computed tomography (CT). The data were processed as multi-planar and three-dimensional reconstructions using Advantage Workstation software. The CT measurements showed that the mean ± standard deviation (SD) FAA of group I was 31.34±5.47º and in group II it was 31.02 ± 4.95º. There were no significant mean difference associations between the length of the femur and the femoral neck angle in either group (P > 0.05). The data suggest that a prosthesis FAA of 31 degrees would be suitable for a wide range of dog sizes.